2002
DOI: 10.1046/j.1540-8167.2002.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Symptomatic Atrial Fibrillation in Patients Enrolled in the Atrial Fibrillation Follow‐up Investigation of Rhythm Management (AFFIRM) Study

Abstract: In a large population of patients with AF at high risk for stroke, individual historic and echocardiographic characteristics failed to distinguish patients based on the frequency of AF. Those with frequent and infrequent AF were similar. Although AF frequency has been suggested as a marker of a focal etiology in young populations with little overt heart disease, it does not seem to be a distinguishing characteristic in older populations at high risk for stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Advantages of restoring SR in cases with AF include a marked relief of symptoms, improved cardiac hemodynamics and a decrease in the number of thromboembolic events. 3,10 The results of the Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) and Rate Control Versus Electrical Cardioversion (RACE) studies showed that the risk of embolism and the relief of symptoms does not decrease after restoring SR. [16][17][18][19][20][21] In the AFFIRM study, patients who had at least 1 other risk factor for stroke and death were randomly assigned to either the rate or rhythm control group. [16][17][18][19][20][21] In that trial, risk factors were: being aged ≥65 years, having systemic hypertension, diabetes mellitus, congestive heart failure, transient ischemic attack, prior stroke, left atrium ≥50 mm, and left ventricular fractional shortening of <25% or left ventricular ejection fraction of <0.40.…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of restoring SR in cases with AF include a marked relief of symptoms, improved cardiac hemodynamics and a decrease in the number of thromboembolic events. 3,10 The results of the Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) and Rate Control Versus Electrical Cardioversion (RACE) studies showed that the risk of embolism and the relief of symptoms does not decrease after restoring SR. [16][17][18][19][20][21] In the AFFIRM study, patients who had at least 1 other risk factor for stroke and death were randomly assigned to either the rate or rhythm control group. [16][17][18][19][20][21] In that trial, risk factors were: being aged ≥65 years, having systemic hypertension, diabetes mellitus, congestive heart failure, transient ischemic attack, prior stroke, left atrium ≥50 mm, and left ventricular fractional shortening of <25% or left ventricular ejection fraction of <0.40.…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of SR in patients with AF for primary prevention were examined in the Atrial Fibrillation Follow-up Investigation of Rhythm Management 15 and Rate Control Versus Electrical Cardioversion 16 studies. These 2 studies showed that the cardioversion of patients with high risk of stroke provided no benefit in terms of embolism, death, and the relief of symptoms over rate control.…”
Section: Discussionmentioning
confidence: 99%
“…In these 2 groups, most of the strokes occurred in patients in whom the warfarin therapy was stopped or in patients with INR <2.0. 15,16 Therefore, effective anticoagulation was recommended to all patients with risk factors for stroke.…”
Section: Discussionmentioning
confidence: 99%
“…We separated the patients into the frequent and the infrequent PAF groups according to the frequency of PAF episodes experienced within the last 6 months. We selected “the last 6 months” in proportion to the AFFIRM study 8 . Indeed, the frequency of PAF was not always constant in each patient.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were divided into two groups according to the frequency of PAF episodes experienced within the last 6 months before electrophysiological study: patients with at least one episode of PAF per month (frequent group, n = 57) and patients with less than one episode of PAF per month (infrequent group, n = 51). This classification was based on that from the AFFIRM study 8 . The duration of PAF history was defined as the time interval from the date of the first episode of PAF to the date of the electrophysiological study.…”
Section: Methodsmentioning
confidence: 99%